Decision support model for solid waste management in a closed-loop supply chain (2021)
The importance of solid waste management is a relevant issue in supply chain management because of the accelerated increase in waste generation, pollution and the need to properly manage waste in companies in a particular way and throughout the whole supply chain in a general way. We present a model that supports decision-making regarding solid waste management (particularly glass packaging), for a manufacturer, considering the perspective of the closed-loop supply chain. The model uses the AHP methodology to define the multiple criteria to be considered in the decision and for the selection of the best alternative available according to those criteria. This model was applied at a glass packaging manufacturer in Colombia. The result of the implementation of the model delivered the waste management strategy (used packaging) that best meets the objectives of the echelon under consideration